5,10,15,20-Tetrakis(4-sulfonatophenyl)porphyrin Zinc and Chloro-aluminum Phthalocyanine Disulfonate in Photodynamic Therapy of Colorectal Adenocarcinoma In Vitro - Hosik, Jakub; Hosikova, Barbora; Kolarova, Hana; Bajgar, Robert (Anticancer research, 2024)
BACKGROUND/AIM: Colorectal cancer (CRC) is one of the most widespread malignancies. One of the alternative therapeutic methods appears to be photodynamic therapy (PDT). MATERIALS AND METHODS: This study investigated the efficiency of 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin zinc (ZnTPPS4) and chloro-aluminum phthalocyanine disulfonate (ClAlPcS2) with two commercial photosensitive compounds 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin (TMPyP) and tetramethylthionine chloride (methylene blue, MB) in PDT for CRC in vitro. In addition to the study of the photodynamic effect on the viability of the colorectal carcinoma cell line HT29, cellular uptake, ROS production, and DNA damage were investigated. RESULTS: All photosensitizers showed good accumulation within HT29 cells, high efficiency in killing the cells, and a concentration-dependent increase in the production of ROS. CONCLUSION: PDT using ZnTPPS4 and ClAlPcS2 may be effective in the treatment of CRC, achieving a similar photocytotoxic effect at much lower concentrations compared to MB.
Keywords: DNA Damage; organokovové sloučeniny; Indoles; DNA fragmentation; kolorektální nádory; Photosensitizing Agents; reaktivní formy kyslíku; HT29 Cells; fotosenzibilizující látky; poškození DNA; porphyrins; Colorectal Neoplasms; adenokarcinom; fotochemoterapie; Colorectal adenocarcinoma; Adenocarcinoma; metaloporfyriny; Reactive Oxygen Species; reactive oxygen species; Humans; Organometallic Compounds; Photochemotherapy; viabilita buněk; Cell Survival; photodynamic therapy; indoly; Metalloporphyrins; buňky HT-29; lidé; phthalocyanines